The role of design houses in the evolution of integrated reporting - Wadee, Zubair (My University, 2022)
Integrated reporting matters. South African companies are at the forefront of integrated reporting (R. G. Eccles, M. P. Krzus, & C. Solano, A, 2019) due to many factors, including the role played by the governance framework King IV, the work of the Integrated Reporting Committee of South Africa (IRCSA) and South Africa's experience with different types of social and environmental reporting (Jill Atkins et al., 2020; De Villiers, Rinaldi, & Unerman, 2014). It is within this context that listed companies face isomorphic pressures in the preparation of the integrated report in search of legitimacy. In response to these external pressures, which are considered to be an external jolt, companies must respond. Their responses are driven by management’s attitude to the change and result in outcomes ranging from inertia where the entity does not change to evolution where there are changes to the systems, processes and culture of the organisation. This study finds that a mechanism by which management of companies that prepare integrated reports respond to the external pressure is by using design houses. The study finds that design houses act as a vector. The design house thus enables management to continue with 'business as usual' thus becoming immune to the external jolt and resulting in very little to no change within the organisation, or the design house may play a role in facilitating evolutionary change, with a range of other outcomes in between these two points.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Commerce to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, 2022
Keywords: Design houses; Integrated reporting; South Africa; UCTD; SDG-8: Decent work and economic growth